الإعلام الجديد في ظل مجتمع المعرفة: قراءة في المفهوم والخصائص - غلاب، نادية (مركز فاعلون للبحث في الأنثربولوجيا والعلوم الإنسانية والإجتماعية, 2019)
The combination of traditional technologies and media from written, audio, and audiovisual to the result of digital media output, which is what is called the new media, the new media technology has not eliminated the role of traditional means of communication in the delivery of information, but developed in a new form, Knowledge and the information age in which the "information" has exceeded the mere fact that it is an idea or media given to be transferred between a sender and a receiver to a commodity or service subject to the laws of supply and demand. In this paper, we seek to understand the new media that has crystallized in the emergence of the knowledge society, which has characterized the knowledge society, in terms of information explosion on the one hand, and technological development on the other, which have also become a feature of the new media compared to traditional media. The research aims to define the concepts of the new media in detail and presentation of the characteristics, and the various factors that helped in its emergence and development, in addition to exposure to the technical means it adopts in transmitting it to the media, in addition to explaining how to shift from the new media to the knowledge society and finally subjected to reflections New media technology on traditional media.
أدت المزاوجة بين تقنيات ووسائل الإعلام التقليدي من مكتوبة، سمعية، سمعية بصرية إلى تمخض ناتج إعلامي رقمي وهو ما يطلق عليه بالإعلام الجديد، فتكنولوجيا الإعلام الجديد لم تلغي الدور الذي حققته وسائل الاتصال التقليدية في توصيل المعلومة بل طورتها في شكل جديد، خاصة في ظل مجتمع المعرفة وعصر المعلومات اللذين تجاوزت فيهما "المعلومة" من مجرد كونها فكرة أو معطى إعلامي يراد نقلها بين مرسل و مستقبل إلى سلعة أو خدمة خاضعة لقوانين العرض والطلب. نسعى من خلال هذه الورقة البحثية إلى الإحاطة بماهية الإعلام الجديد الذي تبلور بظهور مجتمع المعرفة والذي تميز-مجتمع المعرفة- بظاهرتي الانفجار المعلوماتي من جهة والتطور التكنولوجي من جهة أخرى، هاتين الظاهرتين أصبحتا أيضا ميزة من ميزات الإعلام الجديد مقارنة بالإعلام التقليدي. ومن ثمة يسع البحث إلى تحديد مفاهيم الإعلام الجديد بشكل مفصل وعرض خصائصه، ومختلف العوامل التي ساعدت على نشوئه وتطوره، بالإضافة إلى التعرض للوسائل التقنية التي يعتمدها في نقله للمادة الإعلامية، هذا بالإضافة إلى شرح كيفية التحول من الإعلام الجديد إلى مجتمع المعرفة وأخيرا تعرضنا إلى انعكاسات تكنولوجيا الإعلام الجديد على وسائل الإعلام التقليدية.
Keywords: الإعلام الرقمي -- مجتمع المعرفة -- وسائل الإعلام -- العولمة الثقافية